Development of Microsoft Office Virtual Reality (VR) Application with Four-D (4D) Approach - Ismanto, Edi; Al Rian, Rahmad; Septian Alza (Universitas Muhammadiyah Riau, 2024)
Virtual Reality (VR) technology has made significant advancements in recent decades. With its evolving potential, VR has the capability to transform the way we learn, work, play, and interact with the world around us. The development of VR applications for Microsoft Office training holds significant relevance, especially for students of Madrasah Tsanawiyah (MTs) Darul Hikmah Pekanbaru. Microsoft Office training is essential for MTs Darul Hikmah Pekanbaru students as it serves as a practical necessity in preparing them for academic and professional endeavors. One relevant challenge is how to integrate VR technology with appropriate learning methods, such as the Four D (4D) method, to make the training experience more effective and efficient. Therefore, this research aims to identify and address these issues, as well as explore the potential of VR applications with the 4D method to enhance users' practical and intuitive Microsoft Office skills. The development of VR applications for Microsoft Office training using the Four D (4D) method, comprising the Define, Design, Develop, and Disseminate stages, has yielded highly favorable results based on comparisons of measurements from subject matter experts, media experts, and participants. From the measurement and validation results, this VR application has received high feasibility ratings. Subject matter experts rated it 100%, while media experts rated it 91.83%, and participants rated it 96% from the VR application trial.